A cytosolic ferredoxin-independent hydrogenase possibly mediates hydrogen uptake in Trichomonas vaginalis - Smutná, Tamara; Dohnálková, Alena; Sutak, Róbert; Narayanasamy, Ravi Kumar; Tachezy, Jan; Hrdý, Ivan (Current biology, 2022)
Trichomonads, represented by the highly prevalent sexually transmitted human parasite Trichomonas vaginalis, are anaerobic eukaryotes with hydrogenosomes in the place of the standard mitochondria. Hydrogenosomes form indispensable FeS-clusters, synthesize ATP, and release molecular hydrogen as a waste product. Hydrogen formation is catalyzed by [FeFe] hydrogenase, the hallmark enzyme of all hydrogenosomes found in various eukaryotic anaerobes. Eukaryotic hydrogenases were originally thought to be exclusively localized within organelles, but today few eukaryotic anaerobes are known that possess hydrogenase in their cytosol. We identified a thus-far unknown hydrogenase in T. vaginalis cytosol that cannot use ferredoxin as a redox partner but can use cytochrome b5 as an electron acceptor. Trichomonads overexpressing the cytosolic hydrogenase, while maintaining the carbon flux through hydrogenosomes, show decreased excretion of hydrogen and increased excretion of methylated alcohols, suggesting that the cytosolic hydrogenase uses the hydrogen gas as a source of reducing power for the reactions occurring in the cytoplasm and thus accounts for the overall redox balance. This is the first evidence of hydrogen uptake in a eukaryote, although further work is needed to confirm it. Assembly of the catalytic center of [FeFe] hydrogenases (H-cluster) requires the activity of three dedicated maturases, and these proteins in T. vaginalis are exclusively localized in hydrogenosomes, where they participate in the maturation of organellar hydrogenases. Despite the different subcellular localization of cytosolic hydrogenase and maturases, the H-cluster is present in the cytosolic enzyme, suggesting the existence of an alternative mechanism of H-cluster assembly.
Keywords: cytosol; hydrogenasa; cytosolic hydrogenase; hydrogenosome; Hydrogenase; Trichomonas; H-cluster; Ferredoxins; Trichomonas vaginalis; Cytosol; ferredoxiny; Hydrogen; vodík